Economic burden of tuberculosis in Tanzania: a national survey of costs faced by tuberculosis-affected households - Andrew Martin Kilale; Andrea Pantoja; Bhavin Jani; Nyagosya Range; Bernard James Ngowi; Charles Makasi; Melkisedeck Majaha; Chacha Dionis Manga; Sylvia Haule; Amani Wilfred; Pudensiana Hilary; Vishnu Mahamba; et al. (BMC, 2022)
Abstract Background Although tuberculosis (TB) care is free in Tanzania, TB-associated costs may compromise access to services and treatment adherence resulting in poor outcomes and increased risk of transmission in the community. TB can impact economically patients and their households. We assessed the economic burden of TB on patients and their households in Tanzania and identified cost drivers to inform policies and programs for potential interventions to mitigate costs. Methods We conducted a nationally representative cross-sectional survey using a standard methodology recommended by World Health Organization. TB patients of all ages and with all types of TB from 30 clusters across Tanzania were interviewed during July - September 2019. We used the human capital approach to assess the indirect costs and a threshold of 20% of the household annual expenditure to determine the proportion of TB-affected households experiencing catastrophic cost. We descriptively analyzed the cost data and fitted multivariable logistic regression models to identify potential predictors of catastrophic costs. Results Of the 777 TB-affected households, 44.9% faced catastrophic costs due to TB. This proportion was higher (80.0%) among households of patients with multi-drug resistant TB (MDR-TB). Overall, cost was driven by income loss while accessing TB services (33.7%), nutritional supplements (32.6%), and medical costs (15.1%). Most income loss was associated with hospitalization and time for picking up TB drugs. Most TB patients (85.9%) reported worsening financial situations due to TB, and over fifty percent (53.0%) borrowed money or sold assets to finance TB treatment. In multivariable analysis, the factors associated with catastrophic costs included hospitalization (adjusted odds ratio [aOR] = 34.9; 95% confidence interval (CI):12.5-146.17), living in semi-urban (aOR = 1.6; 95% CI:1.0-2.5) or rural areas (aOR = 2.6; 95% CI:1.8-3.7), having MDR-TB (aOR = 3.4; 95% CI:1.2-10.9), and facility-based directly-observed treatment (DOT) (aOR = 7.2; 95% CI:2.4-26.6). Conclusion We found that the cost of TB care is catastrophic for almost half of the TB-affected households in Tanzania; our findings support the results from other surveys recently conducted in sub-Saharan Africa. Collaborative efforts across health, employment and social welfare sectors are imperative to minimize household costs due to TB disease and improve access to care, patient adherence and outcomes.